Phytochemical Studies on the Thorns and Leaves of Canthium parviflorum Lam. - Jose, Beena; Jirovetz, Leopold; Shafi, P.M. (Asian Journal of Chemistry, 2010)
The isolation of taraxerol, d-mannitol, petunidin and long chain ester from the thorns, β-sitosterol, sakuranetin-4'-Oglycoside, long chain acids and alcohols from the leaves of Canthium parviflorum Lam. is being reported for the first time. The compounds were charecterized by spectral analysis and comparison with the authentic sample.